Directing some of the indicators to improve the biomechanical performance of the plane attack in the epee - Aziz Ebrahim, M. A. (World Journal of Sport Sciences, 2012)
The research aims to design a training program in light of the proposed indicators to improve the biomechanical performance of the plane attack in the epee. The research sample (8 epee and saber fencer); search tools and precision measuring device resulted in that the proposed training program had a positive impact in terms of morale indicators biomechanical of the attack aircraft and the training and ballistic vehicle. The training program helped to develop force rapidly and consequently led to increase the speed and momentum. Also, improving the muscles working in the legs helped to increase the momentum during the beginning of the of aviation.